2012
DOI: 10.1111/j.1442-9071.2012.02774.x
|View full text |Cite
|
Sign up to set email alerts
|

Angle closure and angle‐closure glaucoma: what we are doing now and what we will be doing in the future

Abstract: Primary angle-closure glaucoma (PACG) frequently leads to severe vision loss. Prevalence among older Asian populations is high and given global demographics, the number of persons with PACG will increase dramatically in the coming decades. Improvements in imaging of the anterior segment will help us to identify more of those with angle closure, and important clinical trials that are currently underway will provide important evidence to support screening and treatment approaches for PACG. In this manuscript, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 37 publications
(67 reference statements)
0
67
0
3
Order By: Relevance
“…A recent study suggested that gonioscopy should be still considered the goldstandard method in detecting PAC and it cannot be replaced by the anterior segment imaging even if both AS-OCT and UBM can be useful in several circumstances (Barkana et al, 2007;Dorairaj et al, 2012;Friedman et al, 2012;Ishikawa et al, 2000;McKee et al, 2013;Pavlin et al, 1992;Pekmezci et al, 2009;Quek et al, 2011;See, 2009). …”
Section: Anterior Segment Imagingmentioning
confidence: 94%
“…A recent study suggested that gonioscopy should be still considered the goldstandard method in detecting PAC and it cannot be replaced by the anterior segment imaging even if both AS-OCT and UBM can be useful in several circumstances (Barkana et al, 2007;Dorairaj et al, 2012;Friedman et al, 2012;Ishikawa et al, 2000;McKee et al, 2013;Pavlin et al, 1992;Pekmezci et al, 2009;Quek et al, 2011;See, 2009). …”
Section: Anterior Segment Imagingmentioning
confidence: 94%
“…Cataract or clear lens removal is being advocated as initial treatment for PAC and PACG. 73,74 Recent randomized controlled trials have demonstrated that in medically controlled and uncontrolled PACG with coexistent cataract, phacoemulsification alone produces statistically comparable IOP lowering compared with phacotrabeculectomy. 75,76 In medically uncontrolled PACG, phacotrabeculectomy did lower IOP more than phacoemulsification alone.…”
Section: Lens Removal As An Alternative Initial Treatmentmentioning
confidence: 99%
“…The other eye is usually treated with a prophylactic peripheral iridotomy as there is significant risk to the fellow eye. 78 Approximately 20% of all individuals with open angle glaucoma have an IOP within the normal range. This is known as normal tension glaucoma (NTG).…”
Section: Glaucomamentioning
confidence: 99%